DEVELOPMENT OF PROFESSIONAL ABILITIES OF STUDENTS OF MEDICAL EDUCATIONAL INSTITUTIONS BY TEACHING FOREIGN LANGUAGES - Anvarov Alijon Uktamovich (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2023)
Annotation: This article says that by studying foreign languages, we have the opportunity not only to communicate with residents of foreign-speaking countries, but also to study articles and textbooks related to the specialty, to get acquainted with the necessary news on the Internet. With regard to the medical profession and the educational process, the importance of learning a foreign language is currently increasing. In medical institutions, the study of a foreign language is considered an obligatory component of the professional training of a specialist.